PERTUMBUHAN BEBERAPA JENIS BIBIT TANAMAN MANGROVE SEBAGAI BIBIT SIAP TANAM DI BALAI KARHUTLA WILAYAH JAWA BALI NUSA TENGGARA - Endra Primantara, I Ketut; Darmadi, A.A.Ketut; Ginantra, I Ketut (SIMBIOSIS, 2019)
Mangrove forests have important role in coastal ecosystems, for example to overcome marine abrasion, bird nesting sites, forming ecological balance, capturing and localizing sediments, preventing soil acidity and inhibiting sea water intrusion. The success of mangrove reforestation is largely determined by the success in preparing mangrove seedlings. Nursery beds made of bamboo to accommodate 4 species of mangrove seedlings, that are Bruguiera gymnorrhiza , Rhizopora apiculata, Rhizopora mucronata and Rhizopora stylosa with 6 replications and each of 3 individuals of each type. The variables measured were plant height, number of leaves and stem diameter. Statistical analysis with the Costat & Co. program The results showed that the average growth of stem height from the 4 mangrove seedlings measured from 6 -13 MST was 1.5 cm, 1.4 cm, 0.8 cm and 0.7 cm respectively. The average number of leaves from the 4 mangrove seedlings were 0.6, 1.2, 0.6, and 0.6 strands respectively and the average stem diameter of the 4 mangrove seedlings was 0.1 cm. The mangrove seedlings of Rhizopora mucronata and Bruguiera gymnorrhiza species that produced higher growth rates of stem height than others, and Bruguiera gymnorrhiza which produced the highest average number of leaves compared to the other three types. Keywords ; seedlings, mangroves, growth